If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + (-4) = 16 g + -4 = 16 Reorder the terms: -4 + g = 16 Solving -4 + g = 16 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + g = 16 + 4 Combine like terms: -4 + 4 = 0 0 + g = 16 + 4 g = 16 + 4 Combine like terms: 16 + 4 = 20 g = 20 Simplifying g = 20
| x+3x+17=6x+5 | | 3+8x=3x+2-1 | | 4(8g+2w)= | | 50=2.5h+24 | | 5(2(3)-3)=15 | | 3x-2(x-6)=10-4(x-7) | | -10+3r=14-5r | | -7y+3=-15 | | -52+6x=2x+40 | | 12+15a=3a | | 50=2.5+24 | | 5-(2x+1)=10x | | 16(x-2)=8 | | V=5914 | | 96=16v+48 | | 5.7-2=-2.3t+14 | | [Z]=23 | | 190=1.5b^2 | | 4x^3-36x^2-144x=0 | | -2-3x=3x-50 | | x+y+6=50 | | 3(2+1)=9 | | (2*3.14*3)*20= | | 6p-7=-7p+6 | | 66=v+14 | | -10m=12m-44 | | 4+3(x-5)=-17 | | 13(4+x-5)= | | 11x-53=23+15x | | 222=6a-12 | | 30.80=28h | | 0.75(8t+-4)=-2 |